Prevalence of beta-Thalassemia Trait and Abnormal Hemoglobins in Sanliurfa Province in Southeast Turkey - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2014)
Thalassemia is one of the most common hereditary disorders in Turkey, especially in the Mediterranean region of the country. The purpose of this study was to determine the frequency of the beta-thalassemia (beta-thal) trait and abnormal hemoglobins (Hbs) in couples who applied for premarital screening in Sanliurfa Province, in the southeastern region of Turkey, a province with the first reported incidence of beta-thal and abnormal Hbs. In the present study, in order to detect the prevalence of the beta-thal trait and abnormal Hbs in Sanliurfa Province, Turkey, a total of 37,962 couples who applied for premarital screening were analyzed. From January 2011 through March 2014, red blood cell (RBC) counts and Hb fractionation were carried out by a cell counter and high performance liquid chromatography (HPLC), respectively. The prevalence of beta-thal with high Hb A(2) (>3.5%) values was found at rates of 2.44% (n = 1853) in Sanliurfa Province. Additionally, the abnormal Hb rate was 1.57% (1193/75,924), and Hb S (HBB: c.20T > A), Hb C (HBB: c.19G > A) and Hb D- Punjab (HBB: c.364G > C) were reported as 0.50, 0.38 and 0.69, respectively. This study is the first to establish the frequency of beta-thal and abnormal Hbs in Sanliurfa Province, which has the highest birth frequency. We report that the frequency of the beta-thal trait is at a high-risk level compared to other cities in Turkey. Due to the high risk of beta-thal in Sanliurfa Province, a premarital screening program would be of great value in informing parents about offspring with beta-thal.
Keywords: Abnormal hemoglobins (Hbs); beta-thalassemia (beta-thal); premarital screening program; Sanliurfa Province; Turkey; REGION; ADIYAMAN; ANEMIA